Homo ritualis Hindu ritual and its significance for ritual theory - Michaels, Axel 1949- (Oxford University Press, 2016)
"This book describes and analyzes various forms of Hindu rituals and examines various conceptional components of (Hindu) rituals such as framing, formality modality and theories of meaning. It is asked how indigenous terms and notions of ritual modifies ritual theory. The book thus is the first attempt to present a Hindu theory of rituals"--
Keywords: Hinduism / Rituals; RELIGION / Hinduism / Rituals & Practice; Newār; Hinduismus; Ritual; Nepal